Study on the Technology of Preparing Active MgO and MOC from Magnesium Hydroxide - Danchun A; Xueying Xiao; Jing Wen; Jinmei Dong; Weixin Zheng; Chenggong Chang (Kuangchan zonghe liyong, 2022)
The salt lakes in Qaidam area are rich in magnesium resources. Along with the development and utilization of lithium and potassium resources a large amount of magnesium-rich by-products will be produced as by-products. In order to improve the utilization rate of magnesium resources, this article uses Mg (OH)2 prepared from calcium carbide slag and MgCl2 as raw materials to study the effect of the calcination process on the particle size, specific surface area, reactive MgO content and setting time of the calcined product. MOC specimens were prepared from the calcined products. The effects of calcining temperature and raw material ratio on the MOC specimens were studied. The results of the study show that the specific surface area of the calcined product decreases gradually with the increase of the calcination temperature and the extension of the holding time, and the particle size tends to decrease first and then increase. With the increase of calcination temperature and the extension of holding time, the reactive MgO content in the calcined product and the setting time of the calcined product increases gradually. When the calcination temperature of the raw material is 600℃, the molar ratio of reactive MgO to MgCl2 is 6, and the Baume degree of the MgCl2 solution is 27, the compressive strength of the MOC specimen is high, and the compressive strength gradually increases with age.